Association between ACTH stimulation test results and clinical signs in dogs with hyperadrenocorticism treated with trilostane. (October 2021) - Wehner, A.; Glöckner, S.; Weiss, B.; Ballhausen, D.; Stockhaus, C.; Zablotski, Y.; Hartmann, K.
Highlights: Hyperadrenocorticism is a commonly diagnosed endocrine disorder in dogs. Trilostane is the treatment of choice for most affected dogs. The ACTH stimulation test (ACTHST) is a frequently performed monitoring tool. Inclusion of clinical signs in data analysis is important. There was no association between clinical signs and ACTHST results. Abstract: Trilostane is the recommended medical treatment for dogs with hyperadrenocorticicm (HAC). The objective of this study was to investigate the association between ACTH stimulation test (ACTHST) results, and relevant clinical signs, in dogs treated with trilostane. A disease-specific questionnaire was developed, which included the owner's assessment of polydipsia, polyuria, polyphagia, panting, and satisfaction with the treatment, based on a 5-response category rating scale. Forty-nine dogs with HAC were prospectively enrolled. Dogs were grouped according to their recheck appointment (first recheck, 710 days after commencement of treatment or change of trilostane dose; second recheck, 4 weeks after the first recheck; third recheck, performed at 3–6 months intervals once the dog was well controlled). At the recheck appointment, the owner's questionnaire responses were recorded, and an ACTHST was performed, along with urine specific gravity measurement. Linear mixed effects models were used to assess differences among the three recheck time points and to test possible associations between ACTHST results and clinical signs. Significant differences between rechecks were present for stimulated cortisol (first to third recheck, P < 0.001; second to third recheck, P < 0.01), polydipsia (first to second recheck, P = 0.001), polyuria (first to second recheck, P < 0.001; first to third recheck, P = 0.001), and owner satisfaction (first to second recheck, P < 0.001; first to third recheck, P < 0.001). Backward stepwise variable elimination did not identify any significant associations between ACTHST results and clinical signs. Therefore, clinical signs of HAC were not predicted based on the ACTHST results.